Inovasi Pengembangan Kurikulum Pendidikan Dasar untuk Meningkatkan Kualitas Pembelajaran - Fitri Nur Jannah; Siti Maisaroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article aims to explore innovations in elementary education curriculum development that can help students face global challenges. Using qualitative research methods with a case study approach, this research highlights several innovative models that have been implemented in various elementary schools in Indonesia. The results show that the integration of digital technology, project-based learning approaches, and personalized learning play a significant role in increasing engagement and learning effectiveness. This article also identifies key challenges in implementing these innovations and provides recommendations for overcoming existing barriers. Responsive and adaptive curriculum innovations are expected to prepare students with the skills and knowledge needed to succeed in an ever-changing future.Keywords: Curriculum Innovation, Elementary Education, Global Challenges, Globalization, Case Studies